Pengaruh Air Rebusan Daun Salam Terhadap Kadar Asam Urat Pada Lansia Dengan Hiperurisemia : Systematic Literature Review - Nurani Alawiah, Dwi; Ismafiaty, Ismafiaty; Badrujamaludin, Asep (Jurnal Keperawatan Komplementer Holistic, 2024)
Uric acid is the end product of purine metabolism, a component of nucleic acids found in the cell nucleus. The accumulation of crystal deposits in the joint areas is caused by an increase in uric acid levels in the blood, typically resulting from the consumption of purines ranging between 0.5-0.75 g/ml. Elevated levels of uric acid in the blood are referred to as hyperuricemia. Bay leaf is one of the natural remedies that can be used to reduce uric acid levels. Essential oils, tannins, polyphenols, alkaloids, and flavonoids are chemical components found in this plant. Leaves, bark, roots, and fruit of this plant can be utilized as medicine, with side effects such as diuretic and analgesic properties. The purpose of this literature review is to identify the impact of bay leaf decoction on uric acid levels in the elderly with hyperuricemia. The research method involves a literature review that identifies, assesses, and interprets all findings on a research topic. The search strategy includes databases such as Google Scholar, PubMed, ScienceDirect, and Garuda, using keywords such as bay leaf decoction and hyperuricemia. Journal critical assessment is conducted using the JBI Critical Appraisal Tool for quasi-experimental studies. The results of the data analysis review indicate that bay leaf decoction is capable of reducing uric acid levels.